PENERAPAN MODEL PEMBELAJARAN PROBLEM BASEDINSTRUCTION (PBI) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 012 BUKIT LINGKAR KECAMATAN BATANG CENAKU KAB. INHU - Rohandi Rohandi; Mahmud Alpusari; Damanhuri Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This study aims to improve learning outcome IPA class studenst IV SD Negeri 012 Bukit Lingkar Kecamatan Batang Cenaku Kab. Indragiri Hulu 2014/2015 school year. This research subject is student class IV SD Negeri 012 Bukit Lingkar with total student is 20 student. Type of this research is class action research with 2 cycle. The research indicate that teacher activity in cycle I with 70% average and cycle II improve to 90% average. The research result experience improve, before application of learning model problem instruction. In the base score student success 5 person (25%) with 66,1 average, cycle II improve again with student success 18 person (90%) with 82,8 average. All of the improve learning outcome is 65%. Therefore conclusion of this research that hypothesis in this research “ If model learning Problem Based Intruction (PBI) applied than can improve learning outcomes IPA class student IV SD Negeri 012 Bukit Lingkar Kecamatan Batang Cenaku Kab. Indragiri Hulu.” Can be accepted.Keyword : Model Learning Problem Based Instruction (PBI), Learning outcome IPA